Exploring Elaboration in Balinese Music - Sudirana, I (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2021)
In previous publications, gamelan culture has often been associated with heterophonic characteristics. In this paper, I want to show its greater diversity through the analysis of several examples that represent the diversity of music and ensembles in Bali. I also want to demonstrate that the distinction between heterophonic and polyphonic has nothing to do with the melodic characteristics and melodic innovation of Balinese gamelan. In fact, much Balinese music displays polyphonic characteristics. I argue that Balinese music evades general categorization because it often occupies a liminal space between these two textural categories of heterophony and polyphony. In Balinese music, we are faced with a rich and diverse musical culture, which cannot be boxed into a single category.